(untitled) (Texas Journal of Engineering and Technology, 2022)
In this article, the results of the analysis of the types of clothing, colours and styles suitable for women with atypical body shapes, as well as their compatibility with modern fashion, are highlighted based on the analysis of the test questionnaire.